Scandinavian multicenter analysis of patients with pancreatic, ampullary, distal bile duct, or duodenal cancer with liver metastases treated with ablation or resection - Kristina Hasselgren; Ernesto Sparrelid; Marcus Holmberg; Asif Halimi; Oskar Franklin; Per Sandström; Knut Jorgen Labori; Bergthor Björnsson (Next Research, 2026)

Optimal balancing of xylem efficiency and safety explains plant vulnerability to drought - Oskar Franklin; Peter Fransson; Florian Hofhansl; Steven Jansen; Jaideep Joshi (Ecology Letters, 2023)
In vast areas of the world, forests and vegetation are water limited and plant survival depends on the ability to avoid catastrophic hydraulic failure. Therefore, it is remarkable that plants take hydraulic risks by operating at water potentials ( ψ ) that induce partial failure of the water conduits (xylem). Here we present an eco‐evolutionary optimality principle for xylem conduit design that explains this phenomenon based on the hypothesis that conductive efficiency and safety are optimally co‐adapted to the environment. The model explains the relationship between the tolerance to negative water potential ( ψ 50 ) and the environmentally dependent minimum ψ ( ψ min ) across a large number of species, and along the xylem pathway within individuals of two species studied. The wider hydraulic safety margin in gymnosperms compared to angiosperms can be explained as an adaptation to a higher susceptibility to accumulation of embolism. The model provides a novel optimality‐based perspective on the relationship between xylem safety and efficiency.

The mycorrhizal tragedy of the commons - Nils Henriksson; Oskar Franklin; Lasse Tarvainen; John Marshall; Judith Lundberg‐Felten; Lill Eilertsen; Torgny Näsholm (Ecology Letters, 2021)
Trees receive growth‐limiting nitrogen from their ectomycorrhizal symbionts, but supplying the fungi with carbon can also cause nitrogen immobilization, which hampers tree growth. We present results from field and greenhouse experiments combined with mathematical modelling, showing that these are not conflicting outcomes. Mycorrhizal networks connect multiple trees, and we modulated C provision by strangling subsets of Pinus sylvestris trees, assuming that carbon supply to fungi was reduced proportionally to the strangled fraction. We conclude that trees gain additional nitrogen at the expense of their neighbours by supplying more carbon to the fungi. But this additional carbon supply aggravates nitrogen limitation via immobilization of the shared fungal biomass. We illustrate the evolutionary underpinnings of this situation by drawing on the analogous tragedy of the commons , where the shared mycorrhizal network is the commons, and explain how rising atmospheric CO 2 may lead to greater nitrogen immobilization in the future.

Microbial community dynamics alleviate stoichiometric constraints during litter decay - Christina Kaiser; Oskar Franklin; Ulf Dieckmann; Andreas Richter (Ecology Letters, 2014)
Under the current paradigm, organic matter decomposition and nutrient cycling rates are a function of the imbalance between substrate and microbial biomass stoichiometry. Challenging this view, we demonstrate that in an individual‐based model, microbial community dynamics alter relative C and N limitation during litter decomposition, leading to a system behaviour not predictable from stoichiometric theory alone. Rather, the dynamics of interacting functional groups lead to an adaptation at the community level, which accelerates nitrogen recycling in litter with high initial C : N ratios and thus alleviates microbial N limitation. This mechanism allows microbial decomposers to overcome large imbalances between resource and biomass stoichiometry without the need to decrease carbon use efficiency ( CUE ), which is in contrast to predictions of traditional stoichiometric mass balance equations. We conclude that identifying and implementing microbial community‐driven mechanisms in biogeochemical models are necessary for accurately predicting terrestrial C fluxes in response to changing environmental conditions.

Forest fine‐root production and nitrogen use under elevated CO 2 : contrasting responses in evergreen and deciduous trees explained by a common principle - OSKAR FRANKLIN; ROSS E. McMURTRIE; COLLEEN M. IVERSEN; KRISTINE Y. CROUS; ADRIEN C. FINZI; DAVID T. TISSUE; DAVID S. ELLSWORTH; RAM OREN; RICHARD J. NORBY (Global Change Biology, 2009)
Despite the importance of nitrogen (N) limitation of forest carbon (C) sequestration at rising atmospheric CO 2 concentration, the mechanisms responsible are not well understood. To elucidate the interactive effects of elevated CO 2 (eCO 2 ) and soil N availability on forest productivity and C allocation, we hypothesized that (1) trees maximize fitness by allocating N and C to maximize their net growth and (2) that N uptake is controlled by soil N availability and root exploration for soil N. We tested this model using data collected in Free‐Air CO 2 Enrichment sites dominated by evergreen ( Pinus taeda ; Duke Forest) and deciduous [ Liquidambar styraciflua ; Oak Ridge National Laboratory (ORNL)] trees. The model explained 80–95% of variation in productivity and N‐uptake data among eCO 2 , N fertilization and control treatments over 6 years. The model explains why fine‐root production increased, and why N uptake increased despite reduced soil N availability under eCO 2 at ORNL and Duke. In agreement with observations at other sites, the model predicts that soil N availability reduced below a critical level diminishes all eCO 2 responses. At Duke, a negative feedback between reduced soil N availability and N uptake prevented progressive reduction in soil N availability at eCO 2 . At ORNL, soil N availability progressively decreased because it did not trigger reductions in N uptake; N uptake was maintained at ORNL through a large increase in the production of fast turnover fine roots. This implies that species with fast root turnover could be more prone to progressive N limitation of carbon sequestration in woody biomass than species with slow root turnover, such as evergreens. However, longer term data are necessary for a thorough evaluation of this hypothesis. The success of the model suggests that the principle of maximization of net growth to control growth and allocation could serve as a basis for simplification and generalization of larger scale forest and ecosystem models, for example by removing the need to specify parameters for relative foliage/stem/root allocation.

Pine Forest Floor Carbon Accumulation in Response to N and PK Additions: Bomb 14 C Modelling and Respiration Studies - Oskar Franklin; Peter Hgberg; Alf Ekblad; Gran I. gren (Ecosystems, 2003)